Outcome of Ilizarov fixator for non union of femur and tibia in pediatrics and adolescents. (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the functional and radiological outcome of Ilizarov ring fixator for nonunion of femur and tibia in pediatrics and adolescent.Methods: This descriptive study was conducted in Bolan Medical Complex Hospital Quetta, from 3rd February 2016 to 24th February 2019.All paediatrics and adolescent patients with non union femur and tibia meeting the inclusion criteria were operated for Ilizarov ring fixator. Post operative functional and radiological outcome was assessed through AASAMI(Association For The Study And Application Of Methods Of Ilizarov) scoring system at final follow up and graded as Excellent, Good, Fair and Poor.Results: We included 30 patients with mean age 12.7+ 2.16years(range 8 to 15 years).Male children were 25(83.33%) and female 5 (16.67%).Among the participants infected non-union of femur was present in 11 (36.7%), infected non union tibia in 8 (26.7 %), non union femur 9 (30.0 %) and non union tibia in 2 (6.7%).A total of 8 patients (26.7%) had no previous surgeries, 9 (30.0%) patients had only one surgery and 13 (43.3%) had two previous surgeries. Excellent results were achieved in 8(40%) good in 6(20%) and fair in 6(20%) patients with femur Ilizarov. Tibial Ilizarov produced excellent results in 8(80% ) and good results in 2(20% ) patients.Conclusion: Non union femur and tibia in children and adolescent treated with Ilizarov produced excellent and good results in majority of patients. We therefore recommend Ilizarov ring fixator as a first line treatment modality to treat non union of femur and tibia in children.